An online portal for EEE LEAD Program - Long, Xin Yi (2018)
The report reviews the project that I have been doing for my last year of study for a period of eight months. In the first chapter, it gives a background information about the reason behind this project and the objective and scope of this project. In the second chapter, it shows the different software that will be using in this project and their respective descriptions. In the third chapter, it shows how I start off this project with the designing of wireframe. In the fourth chapter is the page design theory and concept that I had used to apply in this project and the various features that can be found. In the fifth chapter, it explains the different functions that this program can do and how I do I achieve them. In the sixth chapter is the database that are being used in this project and its stored procedures. In the seventh chapter consists of the testing that are being carried out to ensure that this program is working. Lastly, it concludes this project and the recommended future implementations that can be carried out. It is hoped that this report will give the reader a better overview of this project and how it aims to help end-users.